The design and optimization of a cryogenic compressed hydrogen refueling process. (18th August 2021) - He, Ming; Lv, Cui; Gong, Linghui; Wu, Jihao; Zhu, Weiping; Zhang, Yu; Zhang, Meimei; Sun, Wentao; Sha, Li
Abstract: Cryo-compressed hydrogen storage has excellent volume and mass hydrogen storage density, which is the most likely way to meet the storage requirements proposed by United States Department of Energy（DOE）. This paper contributes to propose and analyze a new cryogenic compressed hydrogen refueling station. The new type of low temperature and high-pressure hydrogenation station system can effectively reduce the problems such as too high liquefaction work when using liquid hydrogen as the gas source, the need to heat and regenerate to release hydrogen, and the damage of thermal stress on the storage tank during the filling process, so as to reduce the release of hydrogen and ensure the non-destructive filling of hydrogen. This paper focuses on the study of precooling process in filling. By establishing a heat transfer model, the dynamic trend of tank temperature with time in the precooling process of low-temperature and high-pressure hydrogen storage tank under constant pressure is studied. Two analysis methods are used to provide theoretical basis for the selection of inlet diameter of hydrogen storage tank. Through comparative analysis of the advantages and disadvantages of the two analysis methods, it is concluded that the analysis method of constant mass flow is more suitable for the selection in practical applications. According to it, the recommended diameter of the storage tank at the initial temperature of 300 K, 200 K and 100 K is selected, which are all 15 mm. It is further proved that the calculation method can meet the different storage tank states of hydrogen fuel cell vehicles when selecting the pipe diameter. Highlights: A new type of low temperature and high pressure hydrogenation station system is designed. The mathematical model of precooling process of hydrogen storage tank has been established. Two methods for selecting the inlet diameter of storage tank are compared. The inlet diameter of storage tank under design condition is recommended.